Temporal and Age‐Based Variation in Juvenile Sablefish Diet Composition and Quality: Inferences from Stomach Contents and Stable Isotopes. Issue 4 (19th August 2021) - Callahan, Matthew W.; Beaudreau, Anne H.; Heintz, Ron A.; Mueter, Franz J.; Rogers, Matthew C.
Abstract: Prey communities in the North Pacific Ocean have been disrupted by marine heatwaves, and reductions in forage fishes have had notable impacts on upper‐trophic‐level consumers. Little is known about the potential effects of a changing prey base for some commercially valuable fishes, such as Sablefish Anoplopoma fimbria . The objectives of this study were to evaluate temporal and age‐based shifts in diets of juvenile Sablefish, with a focus on understanding their reliance on high‐quality forage fishes. We collected Sablefish from a bay in Southeast Alaska over 2 years (2017–2019) during their first autumn (September–October; age 0), in late winter (March; age 1), and during their second summer (July; age 1). Pacific Herring Clupea pallasii constituted the majority of the Sablefish diet by weight (82.1%) and by frequency of occurrence (40.7%), with variation among months, years, and age‐classes. Stable isotopes corroborated our interpretation of diet composition from stomach contents and indicated that age‐0 Sablefish sampled in October 2017 relied on more depleted carbon sources than other groups, potentially explained by consumption of adult salmon carcasses. Significant relationships between stable isotope ratios and Sablefish length indicated that size‐based diet composition differences were most prevalent during March and July. Sablefish exploited prey taxa of variable quality (0.02–5.3 kJ/g), but mean energy density of consumed prey differed little among years or months (3.62–4.48 kJ/g). Overall, 21% of stomachs sampled were empty, with the percentage of empty stomachs peaking in late winter (46%). Stomach content weights expressed as a percentage of body weight were highest in autumn 2018, when Pacific Herring comprised over 80% of the diets by weight. Consumption of high‐energy prey, such as Pacific Herring, may contribute to rapid growth of Sablefish during the critical prewinter period. If strong Sablefish year‐classes become more frequent with a warming ocean, they will require substantial prey resources to support their growth to adulthood.